Measuring psychotherapeutic processes in the context of psychedelic experiences: Validation of the General Change Mechanisms Questionnaire (GCMQ) - Wolff, Max; Evens, Ricarda; Mertens, Lea Julia; Schmidt, Christopher; Beck, Jessica; Rutrecht, Hans; Cherniak, Aaron D; Gründer, Gerhard; Jungaberle, Henrik (Journal of psychopharmacology, 2024)
Background: Therapeutic and salutogenic effects of psychedelic drugs have been attributed to psychotherapeutic or psychotherapy-like processes that can unfold during the acute psychedelic experience and beyond. Currently, there are no psychometric instruments available to comprehensively assess psychotherapeutic processes (as conceptualized by empirical psychotherapy research) in the context of psychedelic experiences. - Aims: We report the initial validation of the General Change Mechanisms Questionnaire (GCMQ), a self-report instrument designed to measure five empirically established general change mechanisms (GCMs) of psychotherapy—(1) resource activation, (2) therapeutic relationship, (3) problem actuation, (4) clarification, and (5) mastery—in the context of psychedelic experiences. - Methods: An online survey in a sample of 1153 English-speaking and 714 German-speaking psychedelic users was conducted to evaluate simultaneously developed English- and German-language versions of the GCMQ. - Results: The theory-based factor structure was confirmed. The five GCMQ scales showed good internal consistency. Evidence for convergent validity with external measures was obtained. Significant associations with different settings and with therapeutic, hedonic, and escapist use motives confirmed the hypothesized context dependence of GCM-related psychedelic experiences. Indicating potential therapeutic effects, the association between cumulative stressful life events and well-being was significantly moderated by resource activation, clarification, and mastery. Factor mixture modeling revealed five distinct profiles of GCM-related psychedelic experiences. - Conclusion: Initial testing indicates that the GCMQ is a valid and reliable instrument that can be used in future clinical and nonclinical psychedelic research. The five identified profiles of GCM-related experiences may be relevant to clinical uses of psychedelics and psychedelic harm reduction.
Online veröffentlicht: 14. Mai 2024
Gesehen am 28.11.2024